2005
DOI: 10.1021/jp0550558
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of the Hydroxide-Catalyzed P−O Cleavage Reactions of Neutral Phosphate Triesters and Diesters in Aqueous Solution:  Examination of the Changes Induced by H/Me Substitution

Abstract: DFT calculations and dielectric continuum methods have been employed to map out the lowest activation free-energy profiles for the alkaline hydrolysis of representative phosphate triesters and diesters, including trimethyl phosphate (TMP), dimethyl 4-nitrophenyl phosphate (DMNPP), dimethyl hydrogen phosphate (DMHP), and the dimethyl phosphate anion (DMP-). The reliability of the calculations is supported by the excellent agreement observed between the calculated and the experimentally determined activation ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 63 publications
8
41
1
Order By: Relevance
“…4) involved in transferring a proton from water to the diester anion, the predicted rate for the reaction through this mechanism is Ϸ3 ϫ 10 Ϫ19 s Ϫ1 . These comparisons and the associated errors do not allow a clear distinction to be made between the two mechanisms using our data, although recent calculations (13) give very good agreement with the triester-like mechanism. Comparing the rate of reaction of the methyl triester and corresponding diester with hydroxide, we note that the effect of neutralizing the phosphoryl group is to accelerate this reaction by Ϸ10 9 fold.…”
Section: Discussioncontrasting
confidence: 78%
“…4) involved in transferring a proton from water to the diester anion, the predicted rate for the reaction through this mechanism is Ϸ3 ϫ 10 Ϫ19 s Ϫ1 . These comparisons and the associated errors do not allow a clear distinction to be made between the two mechanisms using our data, although recent calculations (13) give very good agreement with the triester-like mechanism. Comparing the rate of reaction of the methyl triester and corresponding diester with hydroxide, we note that the effect of neutralizing the phosphoryl group is to accelerate this reaction by Ϸ10 9 fold.…”
Section: Discussioncontrasting
confidence: 78%
“…The maxima obtained from the enthalpy profiles, which may slightly differ from the maxima arising from DE or DG profiles, were used to locate the relevant transition-state structures in solution. [22] All calculations (including geometry optimizations) were performed in a dielectric continuum by using the multipolar expansion (MPE) [30][31][32][33] model developed at Nancy, with which we did not encounter the convergence problems recently described in geometry optimizations with the polarizable continuum model (PCM). [34,35] Probably, the higher efficiency of the MPE method over the PCM method in geometry optimization calculations comes from the fact that the basic equations of the former model are well adapted to analytically compute the energy derivatives.…”
Section: Methodsmentioning
confidence: 99%
“…[33] Moreover, the MPE method leads to results basically identical to PCM, as shown by Curutchet et al, [36] provided that the same cavity characteristics are assumed, although the MPE model demands significantly less computational time. [33] Preliminary calculations [22] indicated that the MPE solvation code is especially efficient and accurate to model S N 2(P) reactions in solution by providing activation energies (DH°) within good chemical accuracy (< 1 kcal mol À1 ). [22] Therefore, all calculations throughout this work were done by using this model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, phosphate esters have been the subject of extensive experimental 3,6-13 and theoretical [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] studies (though the precise mechanisms of both the solution and enzyme catalyzed reactions remain controversial, see e.g. [6][7][8]12,14,15,25,26,29,[33][34][35] ). In contrast, while there has been some significant work on the hydrolysis of sulfate esters (see e.g.…”
Section: Introductionmentioning
confidence: 99%